A LINGUISTIC TRUTH-VALUE TEMPORAL REASONING (LTR) SYSTEM AND ITS APPLICATION TO THE DESIGN OF AN INTELLIGENT ENVIRONMENT - Zhirui Lu; Juan Augusto; Jun Liu; Hui Wang (International Journal of Computational Intelligence Systems, 2012)
This paper focuses on a linguistic-valued temporal logic based reasoning formalism for dynamically modelling and merging information under uncertainty in some real world systems where the state of a system evolves over time and the transition through states depends on uncertain conditions. We provide forward and backward reasoning algorithms which, respectively, support simulation and query answering. These algorithms are then explained through several examples based on Smart Homes applications.